1992
DOI: 10.1108/01443579210009069
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study of Delivery Speed and Reliability

Abstract: Two distinct models of delivery reliability versus delivery speed are tested. On the basis of data from a survey of 193 manufacturing firms, factors associated with the “planning” systems of firms, such as production‐plan goals achieved, inventory goals achieved, and master schedule performance, were found to have a significant effect on delivery reliability. In follow‐up interviews with 13 plant managers; it was found that “process”‐related factors were associated with delivery speed capabilities. Specificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 12 publications
1
33
0
Order By: Relevance
“…The most consistent predictor was new product introduction. In a later analysis, a delivery performance factor (consisting of volume flexibility, delivery speed, and delivery dependability) was found to be related to growth in ROI, ROS, and Sales (Vickery et al, 1997; see also Handfield and Pannesi, 1992). In contrast, the Narasimhan and Jayaram (1998) study found no relationship between customer responsiveness (a composite measure of minimizing delays in order cycle time and reducing product design time) and firm performance in the North American and European samples.…”
Section: The Research Modelmentioning
confidence: 96%
“…The most consistent predictor was new product introduction. In a later analysis, a delivery performance factor (consisting of volume flexibility, delivery speed, and delivery dependability) was found to be related to growth in ROI, ROS, and Sales (Vickery et al, 1997; see also Handfield and Pannesi, 1992). In contrast, the Narasimhan and Jayaram (1998) study found no relationship between customer responsiveness (a composite measure of minimizing delays in order cycle time and reducing product design time) and firm performance in the North American and European samples.…”
Section: The Research Modelmentioning
confidence: 96%
“…Here delivery speed refers to the ability to deliver products or services faster than other competitors (Handfield & Pannesi, 1992). This definition also includes the Harrison et al, 1999).…”
Section: Delivery Speed (Ds)mentioning
confidence: 97%
“…Rather than goods being held at various points within the chain, they will be moving between these points. Research has shown that companies that have been able to achieve significant reductions in cycle times have been able to translate this into tangible business benefits (Handfield and Pannesi, 1992;Belyea, 2000;Arntzen et al, 1995;Aron, 1998;Brennan, 1998). Despite this potential for providing a source of competitive advantage, it has also recently been shown that the infrastructure necessary to support streamlined product flows lags behind the rapid developments in information technology.…”
Section: Physical Logisticsmentioning
confidence: 99%